The effects of targeted labour market programs for job seekers with occupational disabilities - Nikolay Angelov; Marcus Eliason (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
In this study, we estimate the effects of three targeted labour market programmes (LMPs) on the labour market outcomes of occupationally disabled job seekers. Using propensity score matching, we estimate the average treatment effect on the treated of wage subsi-dies, sheltered public employment, and employment at Samhall, a Swedish state-owned company whose aim is to provide employment for persons with disabilites. The control group consists of individuals who are eligible for the targeted LMPs, but have not (yet) received treatment. Using a rich panel data set, containing demographics as well as health and sickness absence measures, we are able to estimate short- to medium-term effects. Our results show large positive effects of all LMPs on labour income, disposable income and employment, and the effects are relatively persistent. However, consistant with the previous empirical literature, we find considerable locking-in effects, measured by a de-crease in un-subsidized employment. Furthermore, the yearly amounts of disability insur-ance paid decrease as a result of program participation, and the decrease becomes more pronounced with time since treatment start. Finally, the effects on disability insurance prevalence are heterogenous, both with respect to the different LMPs and gender.
Keywords: C21; J14; J23; 330; occupational disability; wage subsidies; locking-in effects; treatment effects